GREEK CONCEPTUALIZATIONS OF PERSIAN TRADITIONS: GIFT-GIVING AND FRIENDSHIP IN THE PERSIAN EMPIRE. (May 2021) - Ellis, Samuel
Abstract: This article examines gift-giving within the Persian empire and its perception in Greek literary sources. Gift-giving in the Greek world was often framed in the language of friendship, and Greek authors subsequently articulated Persian traditions using the language and cultural norms of their intended audience. There were fundamental differences in the concepts of gift-exchange and reciprocity between the Greeks and the Persians. This article will examine Persian traditions of gift-giving followed by Greek traditions of gift-giving, and will argue that the Greek misrepresentation of Persian customs led to numerous misunderstandings in relations between Greek and Persian individuals. The use of Greek descriptive language, rather than more accurate terminology, to describe Persian traditions has hindered our understanding of gift-giving in the Persian empire. In addressing these misconceptions, this article will demonstrate the successful use of gift-giving in the Persian empire and the perils of Greek misrepresentation of foreign customs.